Drug Permeation across the Blood-Brain Barrier: Applications of Nanotechnology - Fakhoury, M.; Takechi, Ryu; Al-Salami, Hani (2015)
The blood-brain barrier (BBB) is a neurobiological frontier that isolates brain tissues from the blood vascular system. Its main role is to protect the brain and the central nervous system from external fluctuations in hormones, nutrients and drugs, while allowing the passage of water and small lipophilic molecules. Diffusion across the BBB can occur through several biological mechanisms, but the most common one is simple diffusion, which mainly depends on the size, lipid solubility and concentration gradient of the molecule. Because of the highly dense network of capillary endothelium cells found in the BBB, most of the drugs are not able to cross this physiological barrier. Delivering therapeutic agents to the brain is thus a big challenge, which may prevent treatment of important neurological diseases. In order to overcome this difficulty, researchers have used nanotechnology to help the passage of drugs across the BBB. Nanotechnology has significantly contributed to the field of biotechnology by improving the strategies for drug delivery, and by providing novel carriers for safe and effective brain targeting. The aim of this review is to discuss in more details the anatomical structure and the functions of the BBB, as well as its significance in neurological diseases. A closer look will be given at the transport mechanisms across the BBB. This review finally explores the most recent advances in the field of nanotechnology for drug delivery in the brain, and gives meaningful examples of delivery systems developed including the micelles, liposomes, dendrimers, microcapsules and polymeric nanoparticles.